The Relationship between Personal Hygiene and the Incidence of Tinea Versicolor among Students at Madrasah Ulumul Quran (MUQ) Pagar Air Islamic Boarding School - Putra, Teuku Romi Imansyah; Yusuf, Muhammad; Maulana, Hafidh; Wali, Amran (Indonesian Journal of Tropical and Infectious Disease, 2025)
Tinea versicolor is an infectious dermatological condition caused by fungi, affecting a substantial proportion of the global population. It is particularly prevalent in tropical regions, including Indonesia. Madrasah Ulumul Quran (MUQ) Pagar Air Islamic Boarding School is a densely populated area where students often exhibit poor hygiene practices, potentially increasing the incidence of the disease. The etiological agent responsible for this infection is the Malassezia furfur species, which can be prevented through the adoption of proper personal hygiene behaviors. This study aims to determine the association between personal hygiene and the incidence of Tinea versicolor at MUQ Pagar Air Islamic Boarding School. This is an observational study using a crosssectional design. Data collection was conducted through interviews using questionnaires. The diagnosis of Tinea versicolor was based on the results of the 10% KOH examination. Sixty students from grades X, XI, and XII participated in the study, of which six were diagnosed with Tinea versicolor. The study found that the majority of the population performed good personal hygiene, with only 10% of the subjects diagnosed with Tinea versicolor. Chi-square analysis revealed a p-value of 0.000 (<0.05), indicating a significant association between personal hygiene and the incidence of Tinea versicolor at MUQ Pagar Air Islamic Boarding School. The majority of students at MUQ Pagar Air Islamic Boarding School practiced good personal hygiene and did not have a Tinea versicolor infection.